Professionals working in operating rooms: a characterization of biological and chemical risks - Carneiro, P. (2019)
BACKGROUND: Health professionals could be at risk of having work-related accidents or health problems. The operating room (OR) is a place where physical, ergonomic, biological, and chemical risks may be present.OBJECTIVE: This study aims to characterize the OR of a hospital regarding occupational risks, particularly biological and chemical. It was also sought to verify if professionals' training about occupational risks has some influence on their safety behaviors.METHODS: The research method was based on a Questionnaire applied to the 214 professionals working at the operating rooms of a hospital in northern Portugal.RESULTS: The results revealed the occurrence of 39% (95% CI [29.3%, 50.7%]) of accidents involving biological material, and 12% (95% CI [6.1%, 21.0%]) of accidents involving chemical material. Not all professionals have had training in occupational risks (64% and 47% reported having had training in biological risks and chemical risks, respectively). A non-statistically significant association was found between having had training in biological/chemical risks and having had an accident involving biological/chemical material (Fisher's exact test, p>0.05). A statistically significant association (X-2 = 25.978, df = 3, p < 0.05) was found between the occurrence of accidents involving biological material and the professional category.CONCLUSIONS: This study allows to characterize the main biological and chemical risks in operating rooms according to the perceptions of professional.